2020
DOI: 10.1016/j.jclepro.2020.122779
|View full text |Cite
|
Sign up to set email alerts
|

A survey-based assessment of how existing and potential electric vehicle owners perceive range anxiety

Abstract: Electric vehicle (EV) owners enjoy many positive aspects when driving their cars, including low running costs and zero tailpipe gas emissions, which makes EVs a clean technology provided that they are sourced through renewable sources, e.g., biomass, solar power, or wind energy. However, their driving behaviour is often negatively affected by the so-called range anxiety phenomenon, i.e., a concern that an EV might not have enough driving range to reach the desired destination due to its limited battery size. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 31 publications
0
54
0
Order By: Relevance
“…As 'range anxiety' is a commonly cited barrier to EV adoption [73], increasing vehicle range has been a key objective for vehicle manufacturers. Larger batteries are needed to increase range, which results in higher emissions in both the vehicle cycle and use phase, the latter due to the adverse effect of the additional battery weight on fuel economy.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…As 'range anxiety' is a commonly cited barrier to EV adoption [73], increasing vehicle range has been a key objective for vehicle manufacturers. Larger batteries are needed to increase range, which results in higher emissions in both the vehicle cycle and use phase, the latter due to the adverse effect of the additional battery weight on fuel economy.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Some scholars have found that strengthening the construction of charging infrastructure can effectively reduce consumers' concerns about the driving range of PEVs and promote the diffusion of NEVs [7][8][9][10][11][12]. However, by the end of 2019, there were only 1.22 million charging infrastructures in China, including 516,000 public charging piles and 703,000 private charging piles [13].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from consumer preferences to make corresponding operational decisions is of great significance for maintaining product competitiveness [20]. At present, most scholars use survey questionnaires [9,10,16,21], system simulations [8,22], or analysis of actual charging data of electric vehicles [15,17,23], in order to study consumers' preferences for charging infrastructure. With the development of communication technology, using online content to investigate public opinions can effectively avoid the complexity of interacting with respondents, making the data collection simple and the sampling rate high (close to 100%) [24].…”
Section: Introductionmentioning
confidence: 99%
“…They are largely used in consumer electronics and more and more widespread in the automotive sector. [3] Today, the use of an electric vehicle is still strongly limited by "range anxiety" [4]. In fact, the drivers' main concerns are related to the kilometric range of the vehicle, limited by the usable energy of batteries if compared to those using fossil fuels, and to the charging time, significantly higher than the time required for refueling.…”
Section: Introductionmentioning
confidence: 99%